2006
DOI: 10.1111/j.1440-1754.2006.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Letters to the Editor

Abstract: In this case study, 36 h of ceftriaxone therapy the 9-year-old girl complained biliary colic with ultrasonography-proven biliary precipitates. We concluded that ceftriaxone-associated biliary pseudolithiasis can be observed within 2 days of starting ceftriaxone therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The majority of studies reported a high dose of at least 100 mg/kg/d [11,12,23,28,30,31,34,35,38]. Four studies reported a daily dose of 50-100 mg/kg [18,[34][35][36]. Pseudolithiasis occurred even in daily doses under 60 mg/kg/d [35] (Table 1).…”
Section: Biliary Tract Lithiasismentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies reported a high dose of at least 100 mg/kg/d [11,12,23,28,30,31,34,35,38]. Four studies reported a daily dose of 50-100 mg/kg [18,[34][35][36]. Pseudolithiasis occurred even in daily doses under 60 mg/kg/d [35] (Table 1).…”
Section: Biliary Tract Lithiasismentioning
confidence: 99%
“…Tuna Kirsaclioglu et al observed that ceftriaxone could lead to stable gallstones and complicating diseases, such as cholecystitis [20]. Fasting (with lithiasis reported in the first week of administration), bed rest (lithiasis reported during the first 5 days), feeding habits, and activity patterns are the factors considered to affect lithiasis [11,36]. A family history of lithiasis has been reported as an important risk factor for the formation of gallstones [36].…”
Section: Biliary Tract Lithiasismentioning
confidence: 99%
See 1 more Smart Citation